A perspective on linseed breeding and varietal development in India: A perspective on linseed breeding and varietal development in India - A L RATHNAKUMAR; DIVYA AMBATI (Journal of Oilseeds Research, 2023)
Linseed (Linum usitatissimum L.) is a traditional oilseed crop of India that represents a valuable alternative for cropping systems because of the high quality of the seed oil, which is being increasingly appreciated by consumers, food, cosmetic and eco-materials and industries. The aim of this study was to understand the linseed breeding and varietal development in India in the past to till now. Linseed is also grown in as many as 70 countries across the globe. Several varieties having high seed yield, oil content, Alpha linoleic acid (omega-3 fatty acid), seed colour, size and colour and resistance to wilt, powdery mildew, Alternaria blight and rust and few insect pests like budfly and Spodoptera have been developed globally. Even, to develop edible grade low (<5%) ALA lines like Solin in Australia and TL 99 in India have also been developed. However, a comprehensive analysis and historic review of the linseed varieties released in India and breeding methods employed in developing them has not been attempted so far. Hence, this paper aims at bringing out the historical fact on number of linseed varieties released and notified in India along with the breeding methods employed so that suitable breeding strategy can be formulated in improving production and productivity of linseed in India.